Chemotherapeutics-Induced Intestinal Mucositis: Pathophysiology and Potential Treatment Strategies - Dahlgren, David; Sjöblom, Markus; Hellström, Per M; Lennernäs, Hans (Frontiers in Pharmacology, 2021)
The gastrointestinal tract is particularly vulnerable to off-target effects of antineoplastic drugs because intestinal epithelial cells proliferate rapidly and have a complex immunological interaction with gut microbiota. As a result, up to 40-100% of all cancer patients dosed with chemotherapeutics experience gut toxicity, called chemotherapeutics-induced intestinal mucositis (CIM). The condition is associated with histological changes and inflammation in the mucosa arising from stem-cell apoptosis and disturbed cellular renewal and maturation processes. In turn, this results in various pathologies, including ulceration, pain, nausea, diarrhea, bacterial translocation sepsis, and sometimes death. In addition to reducing patient quality-of-life, CIM often leads to dose-reduction and subsequent decrease of anticancer effect. Despite decades of experimental and clinical investigations CIM remains an unsolved clinical issue, and there is a strong consensus that effective strategies are needed for preventing and treating CIM. Recent progress in the understanding of the molecular and functional pathology of CIM had provided many new potential targets and opportunities for treatment. This review presents an overview of the functions and physiology of the healthy intestinal barrier followed by a summary of the pathophysiological mechanisms involved in the development of intestinal CIM. Finally, we highlight some pharmacological and microbial interventions that have shown potential. Conclusively, one must accept that to date no single treatment has substantially transformed the clinical management of CIM. We therefore believe that the best chance for success is to use combination treatments. An optimal combination treatment will likely include prophylactics (e.g. antibiotics/probiotics) and drugs that impact the acute phase (e.g. anti-oxidants, apoptosis inhibitors, and anti-inflammatory agents) as well as the recovery phase (e.g. stimulation of proliferation and adaptation).